(untitled) (Global Journal of Human-Social Science, 2017)
Domestic violence, having women as perpetrators, has been on the increase in Nigeria, particularly in the last few years. The increase, largely attributed to the renewed media focus on this aspect of gender-based violence, is often rationalised on the premise of self-defence or revenge attacks by the women. Thus, in what may be regarded as one of the landmark changes in human history, the trend is empirically turning the conventional narratives against men in an African society like Nigeria. Curiously, despite numerous studies that report the preponderance of domestic violence being perpetrated by men against women, the latter are becoming perpetrators of some of the most heinous domestic violations in their marriages. Partially due to the socio/cultural inhibitions-the Nigeria society is a highly patriarchal one, in which men have bloated egos-men generally feel ashamed and sometimes confused when abused by the opposite sex. Though the Violence Against Persons (Prohibition) Bill was signed into law in May 2015, the concern in the public domain, especially by the civil society groups, has always been on the protection of women and girls from violence as exhibited in the initial draft of the bill titled: Violence Against Women (Prohibition).